Challenges and prospects for Central America in a context of Global trade - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The purpose of this paper is to analyze current events and politicies in Central America, to discuss new options and initiatives, and to examine the impact they could have in terms of economic growth, regional integration and trade expansion for that subregion.